MODERN APPROACHES TO ORGANIZING CIVIL PROTECTION IN THE CONTEXT OF EPIDEMICS AND BIOLOGICAL THREATS: LESSONS FROM THE COVID-19 PANDEMIC (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article analyzes modern approaches to civil protection during epidemic and biological threat situations. The study examines the lessons learned from the COVID-19 pandemic and their implications for improving civil defense systems. Key areas investigated include early warning mechanisms, population protection protocols, interagency coordination, and the role of digital technologies in epidemic response. The analysis demonstrates that effective civil protection during biological emergencies requires integrated, multi-level systems combining medical, administrative, and technical capabilities. Based on international experience and Uzbekistan’s pandemic response, the article proposes recommendations for strengthening the national civil protection framework against biological threats.